Anti-diabetic and hypolipidaemic effect of botanicals: a review of medicinal weeds on KNUST campus, Kumasi - Christopher Larbie,Dennis Torkornoo and Jeffrey Dadson (Journal of Applied Pharmaceutical Science, 2014)
In recent times, weeds have been controlled by chemical means and other means because they are seen as plant pests as they compete with “useful” plants for shelter, sunlight, nutrients and water. However, these weeds can serve as medicines for the treatment of several diseases such as diabetes and hyperlipidaemic conditions. This review, therefore creates the awareness of some weeds on KNUST campus, Kumasi-Ghana, which are capable of treating diabetes and hyperlipidaemia. There were sixteen weeds from 11 different families identified with anti-hyperlipidaemic and anti-diabetic properties or both. These same plants are also effective against other ailments such as malaria, toothache, eye problems, among others. Conclusion can therefore be drawn that weeds are valuable medicinal plants and hence, must be preserved.
Keywords: Hyperlipidaemia,Diabetes,Weeds.